Bounds for the Zeros of Polynomials (Analysis in Theory and Applications, 2025)
In this paper, we present certain results on bounds for the zeros of a polynomial. Our results yield some generalizations and refinements of the recently provedresults due to Soleiman and Bidkham, Suhail, Rather and Thakur and other classicalresults also.